Instability and Constraint: Interdisciplinary Essay on the Origin of Social Innovations - Fokas, Nikos (Szociológiai Szemle, 2023)
Within the framework of the present paper we are interested in the circumstances of the origin of social innovations. Presenting and analysing the interdisciplinary literature we may conclude that there really exists a general model in the circumstances of the origin of significant innovations impacting on the whole of some level of hierarchic system. We found that innovations may emerge amid the dissolution, disintegration anarchy, crisis, anomaly, or revolution. In order to remove the political connotations of the above mentioned terms I propose the term instability as a collective for these conditions. It is noteworthy that complex systems may be permanently in state of instability, which may serve as a fundamental source of endogenous creativity in the system.